PERANCANGAN SISTEM PENDAFTARAN PASIEN RAWAT JALAN RUMAH SAKIT MELALUI SHORT MESSAGE SERVICE GATEWAY (Studi Kasus: RS. Panti Wilasa “Dr. Cipto” Semarang) - Toni Wijanarko Adi Putra (Jurusan Teknologi Informasi Universitas Semarang, 2018)
SMS Gateway technology used in the outpatient registration process is an applied technology in the field of information. Outpatient outpatient visits are an indication of the hospital's success in managing the public confidence of doctors and re-control of the hospital. Use of SMS Gateway System aims to facilitate the delivery of information through SMS cheap, short and readable for each recipient. This study aims to provide an outpatient registration system at Rumah Panti Wilasa Hospital